Colours and Dyes from Natural Origin: A Review - R, Dr. Sannd (Journal of Medical Biomedical and Applied Sciences, 2016)
A colour influences our moods and emotions and generally enhances the way in which we enjoy our surround-ings. Colour is introduced into these materials using substances known as dyes and pigments. Natural dyes are colours having several applications in textiles, inks, cosmetics, etc. Nature has gifted us more than 500 dye-yielding plant species. The natural dyes offered any imaginable shade of colour, in great brilliance and with ex-act reproducibility. Natural dyes are less toxic, less polluting, less health hazardous, non-carcinogenic and non-poisonous. This paper explains the information regarding the natural colours and dyes so that they are more uti-lized by the industries for the well being of society.ÃÂ